2019
DOI: 10.1002/ece3.4988
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational paternal effect of adult density inDrosophila melanogaster

Abstract: Notwithstanding recent evidences, paternal environment is thought to be a potential but unlikely source of fitness variation that can affect trait evolution. Here we studied intergenerational effects of males’ exposure to varying adult density in Drosophila melanogasterlaboratory populations. We held sires at normal (N), medium (M) and high (H) adult densities for 2 days before allowing them to mate with virgin females. This treatment did not introduce selection through differential mortality. Further, we rand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…For example, researchers used lab-based manipulations to test predictions of density-dependent selection theory in Drosophila melanogaster (e.g. Mueller 1997;Dasgupta et al 2019). Our study provides some of the first evidence that natural selection can shape collective phenotypes, an assumption that is rarely tested, on a scale that is likely not feasible in a field study.…”
Section: Discussionmentioning
confidence: 94%
“…For example, researchers used lab-based manipulations to test predictions of density-dependent selection theory in Drosophila melanogaster (e.g. Mueller 1997;Dasgupta et al 2019). Our study provides some of the first evidence that natural selection can shape collective phenotypes, an assumption that is rarely tested, on a scale that is likely not feasible in a field study.…”
Section: Discussionmentioning
confidence: 94%
“…Paternal effects have been reported in a diversity of taxa, including arthropods (Adler and Bonduriansky 2013;Polak et al 2017;Zajitschek et al 2017;Gasparini et al 2018;Gilad and Downloaded from https://academic.oup.com/evolut/advance-article/doi/10.1093/evolut/qpac051/6887807 by guest on 16 December 2022 A c c e p t e d M a n u s c r i p t Scharf 2019), mammals (García-Palomares et al 2009;Ng et al 2010;Bromfield et al 2014;Dias and Ressler 2014;Mashoodh et al 2018), fish (Evans et al 2017) or tunicates (Crean et al 2013), as well as in plants (Galloway 2000(Galloway , 2001. These effects have been induced by manipulation of paternal diet quality (Bonduriansky and Head 2007), social environment (Crean et al 2013) or both (Adler and Bonduriansky 2013), population density (Dasgupta et al 2019), or temperature (Huey et al 1995). While these reports have clearly advanced our understanding of paternal effects in general, less is known about how different offspring traits vary in their response, both in daughters and sons.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that housing Drosophila melanogaster adults in different group sizes can produce varied physiological responses. For example, under laboratory conditions, Drosophila melanogaster adults housed at different group sizes exhibit correlated changes in life history (Nandy et al 2016; Leech et al 2017) and sexually selected (Bretman et al 2010, 2011; Nandy and Prasad 2011) traits, with effects extending into the next generation (Dasgupta et al 2016, 2019). Flies subjected to crowding early in adult life have reduced lifespan (Graves and Meuller 1993; Joshi et al 1998) and altered age-independent mortality rate (Joshi and Meuller 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many insect populations in the wild go through major cycles of population fluctuations making insects a relevant study system for such questions. Habitat destruction and climate change induced changes in insect population densities make the matter more relevant not just to scientists with entomological interests but also to public in general (Wagner et Nandy and Prasad 2011) traits, with effects extending into the next generation (Dasgupta et al 2016(Dasgupta et al , 2019. Flies subjected to crowding early in adult life have reduced lifespan (Graves and Meuller 1993;Joshi et al 1998) and altered age-independent mortality rate (Joshi and Meuller 1998).…”
Section: Introductionmentioning
confidence: 99%